Analytical Pyrolysis of Insoluble Products Obtained by Thermolysis of Resins and Asphaltenes of the Oil from the Usinskoye Oil Field; AIP Conference Proceedings; Vol. 2051 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2018 (AMHS’18) - Antipenko V. R. Vladimir; Grinko A. A. Andrey Alekseevich; Golovko A. K. Anatoly; Melenevskiy V. N. Vasily (2018, 2018)
Title screen